De pajem a professora de educação infantil: um estudo sobre a constituição identitária da profissional de creche - Silva, Dilma Antunes (2015)
This research aims to investigate the process of identity formation of teachers in early childhood education working in daycare, specifically those who have started their work in the field as day care takers and child development assistants. The research is justified by the fact that it is still a poorly explored theme in the studies on the field of teaching early childhood education, from zero to three years old. This is a qualitative study based on conceptions of social and historical Psychology. The procedure of research adopted was data collection through non-direct interview policy with focus on narratives of life stories. Apart from a bibliographical study, it was necessary to carry out a survey of the studies on teacher identity presented over the last decade at the GT07 of ANPED, which focuses studies on early childhood education, from zero to six years old. There were 256 papers found during the decade of 2004-2013, amongst them only three are on the theme addressed in this research. Three teachers from early childhood education, working specifically in day care from public municipal de São Paulo participated in this research. After collecting and transcribing their interviews, we proceeded to the thematic analysis of the material. The analysis of the results obtained was based on the following axes: the humble beginnings and the childhood background of educators of kindergarten; their personal and professional trajectories; and the affective dimension of pedagogical practice. The results show that their journeys of personal and professional life and their formative journeys are constituent elements of the professional identity of daycare teachers. It was observed in the discourse of the educators that the initial and continuing teacher development in this field has enabled them to develop a sense of belonging to a group of teachers of basic education. However, as far as the school goes, there is still a hierarchy, reinforced legally, among teachers of different levels, in which the teacher of early childhood education, especially those responsible for children from zero to three years old, is considered less of an "educator" than the others, reinforcing the idea of the prevalence of caution at the expense of education and the non-recognition of the inseparability between these activities, regardless of the education segment